2006
DOI: 10.1016/j.immuni.2006.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal Regulation Couples LFA-1 Conformational Changes to Receptor Lateral Mobility and Clustering

Abstract: The alpha(L)beta(2) integrin (leukocyte function-associated antigen-1 [LFA-1]) is regulated to engage and maintain T cell adhesion. Conformational changes in the receptor are associated with changes in receptor-ligand affinity and are necessary for firm adhesion. Less well understood is the relationship between receptor conformation and the regulation of its lateral mobility. We have used fluorescence photobleaching recovery and single-particle tracking to measure the lateral mobility of specific conformations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

26
173
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(202 citation statements)
references
References 45 publications
26
173
3
Order By: Relevance
“…Our data suggest that the intermediate affinity state observed in the literature for the related β 2 integrin LFA-1 (16)(17)(18)(19)(20) does not have to come from an individual conformational state, but could instead result from a mixture of conformational states. Previous studies showed that LFA-1 binding to ICAM-3, compared with ICAM-1, required more activation as defined by the number of activation agents needed (19)(20)(21).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Our data suggest that the intermediate affinity state observed in the literature for the related β 2 integrin LFA-1 (16)(17)(18)(19)(20) does not have to come from an individual conformational state, but could instead result from a mixture of conformational states. Previous studies showed that LFA-1 binding to ICAM-3, compared with ICAM-1, required more activation as defined by the number of activation agents needed (19)(20)(21).…”
Section: Discussionmentioning
confidence: 49%
“…At the leading edge of migrating T lymphocytes, a distinct population of LFA-1 was defined as in an intermediate affinity state by the exposure of different monoclonal antibody epitopes (16). Lateral mobility measurements of LFA-1 on T cell surfaces suggested an intermediate conformational state with distinct diffusion profile (17). In vitro flow chamber experiments showed that an intermediate affinity of LFA-1 on lymphocytes could be induced by immobilized chemokine (18).…”
mentioning
confidence: 99%
“…It is controversial whether the affinity or avidity state of LFA-1 is involved in the insideout and outside-in signals. A recent publication demonstrated that cytoskeletal regulation couples LFA-1 conformational changes to receptor lateral mobility and clustering; thus, both affinity and avidity states of LFA-1 provide regulation of receptor function on lymphocytes (42). Previous studies reported that LFA-1 ligation can co-stimulate T cells for IL-2 production, cell proliferation, and Th1 polarization (27,(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we demonstrate that the RhoA 23/40 domain is critical for the earliest CCL21-triggered LFA-1 activation events measured in vivo as well as for a CXCL12-induced LFA-1 extension step critical for integrin adhesiveness to ICAM-1 under shear flow, but is not involved in spontaneous or CXCL9-induced LFA-1 adhesiveness to ICAM-1 in human T lymphocytes. We also find that CCL21 and CXCL12, on one hand, and CXCL9 on the other hand, use different modalities to activate LFA-1 adhesiveness, whereas CCL21 and CXCL12 trigger LFA-1 conformational changes before ligand binding and thereby increases the pool of extended LFA-1 readily available for interacting with surface-bound ICAM-1 (10), CXCL9 triggers a unique LFA-1 activation process that takes place without conformational changes before ligand binding and therefore may rely on spontaneously extended subsets of LFA-1 that preexist on T cells and preferentially engage with ICAM-1 (4,39). We also show that an alternative chemokine-independent, PKC-induced pathway of LFA-1 activation also does not trigger integrin conformational extension or integrin clustering before ICAM-1 binding and takes place independently of RhoA.…”
Section: Discussionmentioning
confidence: 99%